Exploring New Museology, Social Museology, and Sociomuseology: A Bibliographic Analysis of Doctoral Theses in Museology at Universidade Lusófona (2021-2023) (Cadernos de Sociomuseologia, 2025)
This article conducted a bibliographic analysis of doctoral theses in Museology from Lusófona University, defended between 2021 and 2023, focusing on the concepts of New Museology, Social Museology, and Sociomuseology. The investigation allowed for the identification of different theoretical and practical approaches of these museological trends, as well as their contributions to the enhancement of intangible cultural heritage and social inclusion. Observing the discussions undertaken by recent doctoral graduates, we noticed that the analyzed concepts serve various contexts and research and work objectives, enriching the academic and professional debate in museology and offering new theoretical and practical perspectives for the field. Through the analysis of 10 theses, it was possible to understand the nuances and intersections among these concepts, highlighting the importance of community participation and sustainable development in contemporary museological practice. The analyzed theses demonstrate the relevance of a critical and democratic museology, aligned with the anti-hegemonic and anti-capitalist ideals that marked the emergence of these movements in the 1960s and 70s.Key-words: New Museology; Social Museology; Sociomuseology; Bibliographic research; Lusófona University.